POSTGRADUATE STUDENTS INFORMATION SEEKING BEHAVIOUR IN THE FACULTY OF MANAGEMENT SCIENCES, BAYERO UNIVERSITY, KANO, NIGERIA - Mohammed, Rabiu Nurudeen (American International Journal of Multidisciplinary Scientific Research, 2020)
The study examines postgraduate student’s information seeking behavior in the faculty of management sciences, Bayero University, Kano, Nigeria. Information play critical role in human daily activities such as school life, work, marital life and any other kind of scenario. The concept of information seeking behavior has attracted researchers’ attention and has been of great concern to stakeholders in the academia. Academic libraries avail information from different sources and formats. Objectively the study examines postgraduate students’ information seeking behavior in order to understand students’ information seeking behavior and provide guide to improve the quality of education and performance. Survey research design were use and the population consist of the entire postgraduate students in the faculty of management sciences at Bayero University, Kano, due to difficulty to reach all the population, purposive sampling were applied which result to the selection of (200) respondents comprising of (50) respondents from each of the four departments and questionnaire were issued to them. From the findings it is obvious that in the course of carrying out their studies postgraduate students seek information as a result of activities they engage such exam preparation, dissertation/thesis work, updating knowledge, lecture notes update, personal reading and general reading. However, the result implies that majority of the respondents use library for information concerning exam preparation while the lowest is for general reading to improve their knowledge. The study conclude that postgraduate students do engage in information seeking behaviour for various reasons even though these are hinder by some obstacles. The study recommends the need for management to improve service delivery in the aspect of electronic library, researchers should be guided easily and educated so as to facilitate easy collection of library materials, users should also be guided to enhance easy retrieval of information, continuous training of library staff should be given attention in order for them to be friendly and give quality service to information seekers and finally problem of poor electricity supply should be addressed to make the environment conducive for learning.